Effectiveness of Green Space Social Functions in Ashta and PIM 3 - Marsella Panggabean; Heru Prasetiyo Utomo (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2026)
Green spaces are increasingly recognized as essential elements in the design of modern commercial areas, not only for improving environmental quality but also for supporting social interaction among urban communities. In large cities with limited green spaces, their presence in shopping centers can enhance visitor comfort and extend the duration of visits, allowing malls to function as social and recreational spaces. This study aims to evaluate the effectiveness of green spaces in optimizing the social functions of public spaces in commercial areas through case studies of Ashta District 8 Mall and Pondok Indah Mall 3 (PIM 3) in Jakarta. The research employs a qualitative descriptive approach using field observations, visual documentation, and semi-structured interviews with 5 respondents selected through purposive sampling. The results show that green spaces at PIM 3 are more effective in supporting social interaction, where 3 out of 3 respondents use the space for group activities such as gathering and socializing. In contrast, green spaces at Ashta District 8 tend to support individual or paired activities, as indicated by 2 out of 2 respondents. Furthermore, all respondents (5/5) stated that the presence of green spaces increases their comfort and encourages longer visits to the mall. These findings indicate that the effectiveness of green spaces in supporting social functions is influenced by design characteristics, availability of seating, vegetation density, and thermal comfort. Green spaces that are more accommodating to group activities and provide better environmental comfort tend to generate higher levels of social interaction.